Determination of Tourist Bus Fares in Batu City Based on Ability to Pay, Willingness to Pay, and Vehicle Operating Cost - Mochammad Suhaji Ismail; Achmad Wicaksono; Agus Dwi Wicaksono (Rekayasa Sipil, 2025)
Batu City often experiences traffic congestion. This congestion is caused by the road network in Batu City needing to be proportional to the number of vehicles present. Therefore, breakthroughs (innovations) are required to reduce traffic jams and make it easier for tourists visiting Batu City to reach tourist areas. However, attention must be given to several important factors, including the community's preference for using the Batu City Tourist Bus and the Willingness to Pay (WTP), Ability to Pay (ATP), and Vehicle Operating Costs (BOK) to determine a fare that aligns with these aspects. The method used is a quantitative approach with frequency distribution analysis techniques, Willingness to Pay (WTP) analysis, Ability to Pay (ATP) analysis, and Vehicle Operating Costs (BOK) analysis. The study results show that 71% of tourists are interested in using the tourist bus, mainly because of the ease and comfort of travel, cost efficiency, tourism development, and flexibility. The tourist bus fare based on ATP is IDR 64,397, and the fare of the two routes based on WTP is IDR 24,219 and IDR 24,730. Then, on the BOK calculation, the fare is IDR 54,972 and IDR 45,450. Therefore, the determined fare for the Batu City Tourist Bus for a single round trip is IDR 30,000, with a government subsidy for the tourist bus's BOK amounting to IDR 329,520,297 per year. This study's results are expected to serve as a consideration for the Batu City Government in determining the fare for the Batu City Tourist Bus.